CCSD(T)-F12 calculations of the IR spectrum of cyanoacetylene HC3N beyond the harmonic approximation - Dargelos, Alain; Pouchan, Claude (Chemical physics letters, 2020)
[Display omitted] •It is the first complete theoretical study of the IR spectrum of HC3N.•We propose an ab-initio spectrum with the assignment of all bands. The high-resolution infrared spectrum of HC3N has been the subject of numerous experimental studies. However, none of these studies has been based on high-quality theoretical work. On the basis of an anharmonic potential CCSD(T)-F12/aug-cc-pVTZ and the use of a pure variational method (VCI) the IR spectrum of HC3N was calculated between 200 and 4800 cm−1. These calculations make it possible, on the basis of the positioning of the bands and the calculation of their intensity, to revisit the entire IR spectrum and to assign a large part of it, overtones, combinations bands and hot bands to the experimental observations.